KCl -Permeabilized Pancreatic Islets: An Experimental Model to Explore the Messenger Role of ATP in the Mechanism of Insulin Secretion - Pizarro-Delgado, Javier (PLoS One, 2015)
Our previous work has demonstrated that islet depolarization with KCl opens connexin36 hemichannels in β-cells of mouse pancreatic islets allowing the exchange of small metabolites with the extracellular medium. In this study, the opening of these hemichannels has been further characterized in rat islets and INS–1 cells. Taking advantage of hemicannels’opening, the uptake of extracellular ATP and its effect on insulin release were investigated. 70 mM KCl stimulated light emission by luciferin in dispersed rat islets cells transduced with the fire-fly luciferase gene: it was suppressed by 20 mM glucose and 50 μM mefloquine, a specific connexin36 inhibitor. Extracellular ATP was taken up or released by islets depolarized with 70 mM KCl at 5 mM glucose, depending on the external ATP concentration. 1 mM ATP restored the loss of ATP induced by the depolarization itself. ATP concentrations above 5 mM increased islet ATP content and the ATP/ADP ratio. No ATP uptake occurred in non-depolarized or KCl-depolarized islets simultaneously incubated with 50 μM mefloquine or 20 mM glucose. Extracellular ATP potentiated the secretory response induced by 70 mM KCl at 5 mM glucose in perifused rat islets: 5 mM ATP triggered a second phase of insulin release after the initial peak triggered by KCl-depolarization itself; at 10 mM, it increased both the initial, KCl-dependent, peak and stimulated a greater second phase of secretion than at 5 mM. These stimulatory effects of extracellular ATP were almost completely suppressed by 50 μM mefloquine. The magnitude of the second phase of insulin release due to 5 mM extracellular ATP was decreased by addition of 5 mM ADP (extracellular ATP/ADP ratio = 1). ATP acts independently of K(ATP) channels closure and its intracellular concentration and its ATP/ADP ratio seems to regulate the magnitude of both the first (triggering) and second (amplifying) phases of glucose-induced insulin secretion.